"Coronavation: Keep Calm, and Carry On". (April 2021) - Seales, William Brent
In this essay, I summarize a few ideas inspired by my involvement in the "Coronavation" working group, which spanned 2020's COVID-19 crisis. Health-care practitioners, computer scientists, and engineers alike, we strive to meet the challenges associated with practice under threat of pandemic with the same ideals driving the rapid, positive developments in health care today: innovation, collaboration and technology convergence, and acquisition of valuable data that leads to better approaches and new ideas. The ideas sketched here, forged by the need for practical pandemic responses, are rooted in those ideals.